The use of a holistic focus of attention to improve standing long jump performance among NCAA track and field athletes - Zhuravleva, T.; Aiken, C. A.; Becker, K. A.; Lin, P.-C.; Sampson, J. J. (International Journal of Sports Science & Coaching, 2023)
Research on attentional focus has consistently shown that an external focus (EF) is superior to an internal focus (IF) for performance with novice performers or learners. When examining experienced performers, the findings have been ambiguous with various attentional focus types proving to be beneficial. Recent research suggests that coaches utilize a combination of attentional focus strategies when instructing highly skilled throwers in track and field. In addition to the traditional EF and IF, a holistic focus (HF) has been found to enhance performance similar to that of an EF. The purpose of the current study was to investigate attentional focus manipulations (i.e. IF, EF and HF) among NCAA Division I track and field athletes. Sixteen females performed a standing long jump under three attentional focus conditions in an outdoor long jump sand pit with an orange cone placed 5-m from the starting line. Participants performed three jumps under each focus condition in a counterbalanced order, nine jumps in total. Focus adherence was measured after each condition. Athletes also reported their preferred attentional focus at the conclusion of the study. A repeated-measures ANOVA was used to analyze jump distance and adherence. It was observed that a HF led to significantly longer jump distances than an IF (p < .01). No other significant differences for condition were observed for distance (p > .05). These results suggest that a HF enhanced standing long jump performance among highly skilled individuals and can be used to enhance performance.